Magnetoresistive Sensors: Printable and Stretchable Giant Magnetoresistive Sensors for Highly Compliant and Skin‐Conformal Electronics (Adv. Mater. 12/2021). Issue 12 (23rd March 2021) - Ha, Minjeong; Cañón Bermúdez, Gilbert Santiago; Kosub, Tobias; Mönch, Ingolf; Zabila, Yevhen; Oliveros Mata, Eduardo Sergio; Illing, Rico; Wang, Yakun; Fassbender, Jürgen; Makarov, Denys
Abstract : In article number 2005521, Denys Makarov and co‐workers demonstrate skin‐compliant, stretchable, and printable giant magnetoresistive sensors that can operate in low magnetic fields of 1 mT under extreme mechanical deformations of bending radii of up to 16 μm and 100% stretching. They highlight the application potential of these devices in augmented reality settings, with a sensor‐functionalized finger conducting remote and touchless control of virtual objects.